Investment Priority Setting Workshop on CSA in Mali - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
In Mali, a first workshop has been carried out between the 18th and 19th of November 2014. The event gathered 30 participants representing ministries, local governments, research institutions, NGOs, funders, in order to prioritize 10 to 15 CSA practices. Photos: S. Touré (CCAFS West Africa)